Antimicrobial Therapy as a Risk Factor of Multidrug-Resistant Acinetobacter Infection in COVID-19 Patients Admitted to the Intensive Care Unit - P. Mihalov; J. Hodosy; A. Koščálová; M. Čaprnda; M. Kachlíková; J. Jurenka; M. Bendžala; P. Sabaka (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Multidrug-resistant Acinetobacter (MDR-Ab) is one of the most important pathogens causing superinfections in COVID-19 patients hospitalised in the intensive care unit (ICU). The occurrence of MDR-Ab superinfection significantly impairs the prognosis of patients in the ICU. Overuse of antibiotics in COVID-19 patients might contribute to the risk of developing MDR-Ab infection. Objective. The objective was to assess the role of prior antibiotic exposure as an independent predictor of MDR-Ab infection in COVID-19 patients admitted to the ICU. Methods. We conducted a retrospective cohort study in 90 patients admitted to the ICU of the Department of Infectology and Geographical Medicine, University Hospital in Bratislava, for respiratory failure due to COVID-19 between 1 September 2021 and 31 January 2022 (delta variant predominance). Patients underwent regular microbial screening. Superinfection was defined as infection occurring ≥48 h after admission. We assessed the role of prior antibiotic exposure and other factors as independent predictors of MDR-Ab isolation. Results. Fifty-eight male and 32 female patients were included in the analysis. Multidrug-resistant bacteria were cultured in 43 patients (47.8%), and MDR-Ab was isolated in 37 patients. Thirty-three (36.7%) patients had superinfection caused by MDR-Ab. Fifty-four (60%) patients were exposed to antibiotics prior to MDR-Ab isolation; of those, 35 (64.8%) patients received ceftriaxone. Prior exposure to ceftriaxone (odds ratio (OR) 4.1; 95% confidence interval (CI) 1.4–11.9; P<0.05), tocilizumab therapy (OR 4.7; 95% CI 1.3–15.0; P< 0.05), and ICU length of stay exceeding 11 days (OR 3.7; 95% CI 1.3–10.3; P< 0.05) were independent predictors of MDR-Ab infection. Conclusions. Prior exposure to ceftriaxone increases the risk of MDR-Ab infection in COVID-19 patients admitted to the ICU. Our findings suggest that antibiotic use in COVID-19 patients admitted to the ICU should be restricted to patients with documented bacterial superinfection.